Effectiveness of Project Based Learning Integrated STEM in Physics Education (STEM-PJBL): Systematic Literature Review (SLR) - Roslina Roslina; Achmad Samsudin; Winny Liliawati (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2022)
This study aims to review 36 articles from reputable international journals such as indexed by Scopus, Web of Science (WoS) and SINTA, which explains the Effectiveness of Project Based Learning Integrated STEM in Physics Education. The articles selected for review were the ones published in the last eight years, from 2015 to 2022. The research approach used was a Systematic Literature Review (SLR). This study analyzed the representation of research according to their general characteristics consists of type of publication, year of publication, research approach and educational level. This study also analyzes the effectiveness STEM-PJBL in physics education based on the results of the reviewed research articles. The results show that the use of STEM-PJBL has a positive impact on cognitive, skills and attitude aspects and that STEM-PJBL can be integrated into media or materials teaching such as modulary,worksheet, the implementation of STEM with robots, as well as teacher awareness. So it can be used by teachers as input to apply STEM-PJBL in during physics learning.